TOXICITY OF SOME INSECTICIDES ON DIFFERENTS LIFE STAGE OF Musca domestica L. (Muscidae : Diptera) - Salim J. Jarjees; Ibrahim A. Hassan (Mesopotamia Journal of Agriculture)
The Neporex dissolved in acetone was the most toxic to the eggs, the LC50 with the toxicity of 0.006 followed by the Lannate, 0.007 then, the Ageta, 0.0118. Also the eggs showed a homogenous response to the Neporex dissolved in water and acetone. Neporex dissolved in water and Acetone had the maximum degree of LC50 (0.004 and 0.002) and (0.007 and 0.006) for the first and third instar larvae, respectively Lannate had the maximum degree of toxicity to pupae compared with Neporex and Ageta. The LC50 with acetone had a toxicity of 0.004 followed by Neporex and Ageta. Their toxicity to the adult insect showed that the Ageta and Lannate had the same effect of adult stage. The LC50 dissolved in water and acetone had a toxicity of 0.03 and 0.002 respectively. The Neporex had the least degree when dissolved in water. The LC50 had a 0.005 and when dissolved in acetone gave 0.002 . The result showed that the Neporex had the maximum rate (68.7%) of killing all the stages by direct application when applied at a concentration of 0.007 and the minimum rate (29.00%) when sprayed at 0.001 followed by Lannate then Ageta. The predominant stage being affected by various concentrations was the first instar larvae wich gave 52 % followed by adult, then third instar ,and the pupae, while the less effect was the egg stage were approached 33%. The maximum rate of killing of first larval stage by dissolving the Neporex in water and acetone at 0.007 concentration, last 100% followed by the third larval stage, while the minimum killing rate was 13.3% for both egg and pupal stages when Ageta dissolved in water and acetone. In case of biats the Neporex gave the highest killing rate of the first larval stage when dissolved in acetone by a concentration of 0.007 was 93.3% followed by the third larval stage when dissolved in water at a concentration of 0.007 which reached 91.1% while the least rate was both egg and pupal stages when the Ageta insecticide was dissolved in water and acetone.